Emergence of International and Local Clothing Brands in Bangladesh and Its Impact on Consumers - Baten, Abdul; Ishtiaque, Ahmed; Sarwar, Adib (Asian Business Review, 2018)
There are Boutique outlets popping up in almost all major traffic areas throughout the city. Studies found that customers often perceive foreign brands differently than local brands. Consumers in developed countries specifically have a preference in locally made products than foreign made products. On the other hand, in developing countries like Bangladesh, India, Pakistan etc. products from foreign countries are preferable than domestic products. The perception is that foreign clothing brands will impress others and increase the social status as they represent modern fashion and a sense of socio-economic class. In developing countries consumers have different expectations from different to global brands.